Layer-by-Layer Molecular Assemblies for Dye-Sensitized Photoelectrosynthesis Cells Prepared by Atomic Layer Deposition - Wang, Degao; Sheridan, Matthew V; Shan, Bing; Farnum, Byron H; Marquard, Seth L; Sherman, Benjamin D; Eberhart, Michael S; Nayak, Animesh; Dares, Christopher J; Das, Atanu K; Bullock, R. Morris; Meyer, Thomas J (Journal of the American Chemical Society, 2017)
In a dye sensitized photoelectrosynthesis cell (DSPEC), the relative orientation of the catalyst and chromophore plays an important role in determining the device efficiency. Here we introduce a new, robust atomic layer deposition (ALD) procedure for the preparation of molecular chromophore–catalyst assemblies on wide bandgap semiconductors. In this procedure, solution deposited, phosphonate derivatized metal complexes on metal oxide surfaces are treated with reactive metal reagents in the gas phase by ALD to form an outer metal ion bridging group, which can bind a second phosphonate containing species from solution to establish a R1-PO2-O-M-O-PO2-R2 type surface assembly. With the ALD procedure, assemblies bridged by Al(III), Sn(IV), Ti(IV), or Zr(IV) metal oxide units have been prepared. To evaluate the performance of this new type of surface assembly, intra-assembly electron transfer was investigated by transient absorption spectroscopy, and light-driven water splitting experiments under steady-state illumination were conducted. A SnO2 bridged assembly on SnO2/TiO2 core/shell electrodes undergoes light-driven water oxidation with an incident photon to current efficiency (IPCE) of 17.1% at 440 nm. Light-driven water reduction with a ruthenium trisbipyridine chromophore and molecular Ni(II) catalyst on NiO films was also used to produce H2. Compared to conventional solution-based procedures, the ALD approach offers significant advantages in scope and flexibility for the preparation of stable surface structures.